Roles of age, gender and psychological difficulties in adolescent mentalizing. (July 2019) - Poznyak, Elena; Morosan, Larisa; Perroud, Nader; Speranza, Mario; Badoud, Deborah; Debbané, Martin
Abstract: Introduction: Adolescence is a critical period for the development of mentalizing – the imaginative capacity to understand one's own and others' behaviour in terms of underlying mental states. Yet, factors and mechanisms underlying individual differences in adolescent mentalizing remain poorly understood. This exploratory study examined whether and how a) age and gender and b) psychological difficulties correlate with mentalizing performance in adolescents from the general population. Methods: 89 adolescents from Geneva, Switzerland (54 females, age 12–17 years) completed a computerized task of mentalizing and a self-report measure of psychopathology. Results: Mentalizing performance improved with age. Males showed lower scores on the mentalizing task and made more hypermentalizing errors than females. The main findings revealed a negative association between mentalizing performance and self-reported attention problems. Post-hoc analyses further demonstrated that self-reported attentional difficulties were particularly associated with weaker scores on items requiring mentalizing about intentions, while self-reported withdrawal/depression symptoms were particularly associated with weaker scores on items requiring mentalizing about emotions and thoughts. Conclusion: The present study highlights a negative association between attentional difficulties and mentalizing performance in community adolescents. Moreover, it provides preliminary evidence suggesting that age, gender and psychological difficulties can be distinctively associated with patterns of correct and incorrect mentalizing in community adolescents. Implications for future research and clinical practice are discussed.